2015
DOI: 10.7554/elife.09183
|View full text |Cite
|
Sign up to set email alerts
|

LynA regulates an inflammation-sensitive signaling checkpoint in macrophages

Abstract: Clustering of receptors associated with immunoreceptor tyrosine-based activation motifs (ITAMs) initiates the macrophage antimicrobial response. ITAM receptors engage Src-family tyrosine kinases (SFKs) to initiate phagocytosis and macrophage activation. Macrophages also encounter nonpathogenic molecules that cluster receptors weakly and must tune their sensitivity to avoid inappropriate responses. To investigate this response threshold, we compared signaling in the presence and absence of receptor clustering u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(93 citation statements)
references
References 73 publications
11
82
0
Order By: Relevance
“…1C and Supplemental Fig. S4A), as previous reports indicate, showing the early activation of SFK, including LYN, in macrophages and B cells (26,27). On the other hand, LYN activity was gradually decreased for the duration of over 12 h after oAb 1-42 exposure (Fig.…”
Section: Lyn Kinase Is Activated In Neuronal Cells By Oab Treatment Asupporting
confidence: 84%
“…1C and Supplemental Fig. S4A), as previous reports indicate, showing the early activation of SFK, including LYN, in macrophages and B cells (26,27). On the other hand, LYN activity was gradually decreased for the duration of over 12 h after oAb 1-42 exposure (Fig.…”
Section: Lyn Kinase Is Activated In Neuronal Cells By Oab Treatment Asupporting
confidence: 84%
“…6b-g). We found that CSK and LYN, which regulate the Src family kinase response to weak signals and act as a rheostat for inflammatory signaling 39 are downregulated along this trajectory, making the macrophages less inflammatory as they transition. A concurrent upregulation of CIITA and HLA-DQA1 suggests an increasing role in antigen presentation.…”
Section: Cluster-specific Expression Of Genes Associated With Diseasementioning
confidence: 99%
“…The SFKs, which in myeloid cells typically include Fgr, Fyn, and two splice forms each of Hck and Lyn, may also have positive and negative functions (12, 1719). Layered onto the traditional positive-and negative-regulatory roles of the SFKs, we have shown that activated LynA (the longer of the two Lyn splice forms) is rapidly and specifically targeted for polyubiquitination and degradation, forming the basis of a signaling checkpoint that blocks spurious macrophage activation (20). The mechanism preferentially targeting LynA for polyubiquitination and the molecular basis of this selectivity have not been elucidated previously.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike Dectin-1 and FcγR signaling in macrophages, which is typically triggered in the context of pathogen-induced µm-scale clusters of receptors (5, 9, 20), mast-cell FcεR signaling has a low threshold for activation--small or even monovalent antigen-IgE complexes are sufficient to induce a signaling response (21, 22). Like macrophages, mast cells express LynA, and this disparity in receptor sensitivity has not previously been explained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation